Application of the plasma surface sintering conditions in the synthesis of ReBx–Ti targets employed for hard films deposition in magnetron sputtering technique. (February 2022) - Wicher, Bartosz; Chodun, Rafał; Trzcinski, Marek; Lachowski, Artur; Nowakowska-Langier, Katarzyna; Ibrahim, Samih Haj; Jaroszewicz, Jakub; Kubiś, Michał; Grzanka, Ewa; Zdunek, Krzysztof
Abstract: Preparation of a ternary ReBx –Ti compound within a single magnetron target, forming a plasma surface sintering (PSS) conditions, were investigated. An ionized‑neon pressure of 40 Pa induced sintering power pulses (Ei ) with energies of up to 3.1 kJ, which resulted in a low-porosity rhenium boride (3.2%) structure within a solid titanium matrix (ReBx –Ti). The prepared targets showed promising resistance to high temperatures (5.45 mm 2 /s of thermal diffusivity), after the PSS process at a temperature above 2100 °C. These as-surface-sintered magnetron targets were further used in gas injection magnetron sputtering to obtain Re–B–Ti films characterized by an enhanced deposition rate (120 nm/min). Quantitative analysis of these films revealed that the B/Re ratio was in deficit in comparison to the stoichiometry of as-prepared cathode materials. A multiple-chemical-bond state showed the occurrence of ReB, TiB, BB, TiTi, TiO, and BO phases, of which TiB2 and ReB2 were dominant, forming therefore a glass-like structure. All gathered data indicated a maximum Vickers microhardness value (36.4 GPa), emphasizing the valuable mechanical response of the deposited Re–B–Ti films, as well as the retaining of their good self-passivation effect, attributed by the oxide phases. Graphical abstract: Unlabelled Image Highlights: ReBx powder as a cathode material was sintered to employ it in magnetron sputtering. ReB2 and TiB2 amorphous phases were identified in the deposited Re–B–Ti films. Mechanical study of Re–B–Ti films was proven up to 36.4 GPa of microhardness result. A self-passivation effect was revealed through the nucleation of Ti-O and B-O states. High deposition rate (~120 nm/min) emphasized strength of surface sintered cathode.